Smooth muscle cells and fibroblasts in the ascending aorta exhibit minor differences between embryonic origins in angiotensin II-driven transcriptional alterations - Sohei Ito; David B. Graf; Yuriko Katsumata; Jessica J. Moorleghen; Chen Zhang; Yanming Li; Scott A. LeMaire; Ying H. Shen; Hong S. Lu; Alan Daugherty; Hisashi Sawada (Scientific Reports)
Abstract Thoracic aortopathy is influenced by angiotensin II (AngII) and exhibits regional heterogeneity with the ascending aorta being particularly susceptible. In this region, smooth muscle cells (SMCs) and selected fibroblasts originate from the second heart field (SHF) and cardiac neural crest (CNC). While our previous study revealed a critical role of SHF-derived cells in AngII-mediated aortopathy, the contribution of CNC-derived cells remains unclear. To investigate lineage-specific responses to AngII, Mef2c-Cre R26RmT/mG mice were infused with AngII. Ascending aortas were harvested at baseline or after 3 days of infusion, representing the prepathological phase. Cells were sorted based on their embryonic origins and single-cell RNA sequencing was performed. Transcriptomic analysis revealed significant changes in both SHF- and nSHF-derived SMCs following short-term AngII infusion, although differences between the origins were modest. Similarly, fibroblast transcriptomes exhibited notable changes, yet lineage-specific differences remained modest, except for a newly identified fibroblast subpopulation where extracellular matrix-related genes such as Eln and Col3a1 were downregulated in SHF-derived fibroblasts compared to nSHF-derived fibroblasts. These findings suggest that while fibroblasts in the new subcluster exhibit lineage-specific extracellular matrix-related differences, overall transcriptomic variations between SHF- and nSHF-derived cells in response to AngII remain modest during the prepathological phase of AngII-induced thoracic aortopathy.